2020
DOI: 10.1109/ojap.2020.3006842
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Splitting-Based CN-FDTD for Modeling 2D Material Nanostructure Problems

Abstract: Incorporating a truncation of the complex-frequencyshifted perfectly matched layer (CFS-PML), the direct-splittingbased Crank-Nicolson finite-difference time-domain (CNDS-FDTD) is developed and applied to the infrared two-dimensional layered material (2DLM) black phosphorous (BP) metasurface implementations on the all-dielectric nanostructure. To improve extremely low efficiencies in solving infrared terahertz (THz) problems with the few-atomic-layer thickness of 2DLMs, the CFS-CNDS-FDTD is proposed in demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The formulas shown in [1] is completely wrong on closer inspection. To be more specifically, for example, eqs.…”
Section: B Incorrect Mathematical Derivations For Cnds-pmlmentioning
confidence: 98%
See 4 more Smart Citations
“…The formulas shown in [1] is completely wrong on closer inspection. To be more specifically, for example, eqs.…”
Section: B Incorrect Mathematical Derivations For Cnds-pmlmentioning
confidence: 98%
“…The authors claimed that they have developed the CNDS-FDTD algorithms along with its PML implementation in [1], while it is not the truth. These two studies can be respectively found in [2] and [42].…”
Section: A No Innovations In Mathematical Derivationsmentioning
confidence: 99%
See 3 more Smart Citations